Creating Fiscal Space for Poverty Reduction in Ecuador : A Fiscal Management and Public - Expenditure Review - World Bank (Washington, DC: World Bank and the Inter-American Development Bank, 2012)
This report consists of two volumes. Volume I examines whether, and how, the core goals of public expenditure management, i.e., balanced fiscal aggregates, resource allocations to strategic sectors, and equity and microeconomic efficiency of public spending are met in Ecuador. Volume II presents sector studies on fiscal sustainability, the fiscal rules, education, health, pensions, the results of a national teachers tracking survey, water and sanitation, electricity, telecommunications and oil. Volume II deals with sectoral policies, and their link to fiscal management. It identifies the most efficient and cost-effective interventions in the social sectors, while making an optimal use of the reduced and available fiscal space. The study also recognizes the importance of political constraints, and the difficulties of setting steady rules in a non-cooperative game among national political actors that are particularly reflected in budget allocations.